Study of the preferences of doctors and pharmacists regarding medicines for the treatment of diseases of the peripheral nervous system - T. S. Brytanova; T. P. Zarichna; A. S. Hotsulia; Yu. V. Shostak (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2022)
The aim of the work is to assess the preferences of doctors and pharmaceutical workers regarding drugs for the treatment of diseases of the peripheral nervous system in order to optimize the medical supply of the population.